Community Perception About Roof Garden in Malang City Building - Bachtiar Rachmad Sugiyono; Bambang Tri Rahardjo; Bagyo Yanuwiadi (The Indonesian Green Technology Journal, 2020)
Abstract The research is about perception of community about roof garden in Malang City. In this research, identification of perception is from benefits of roof garden variables, that is : ecology variable, aesthetics variable, economy variable, 3R variable, cultivation variable, and plant pests and diseases variable. The result of this research is most of  the perspondents have agrees about benefit of roof garden variable and doubt in economy variable and 3R variable. The research is useful for parties who will do the making of roof garden in multi-storey building.